How to Modulate Catalytic Properties in Nanosystems: The Case of Iron–Ruthenium Nanoparticles. Issue 6 (10th April 2014) - Kelsen, Vinciane; Meffre, Anca; Fazzini, Pier‐Francesco; Lecante, Pierre; Chaudret, Bruno
Abstract Ultrasmall FeRu bimetallic nanoparticles were prepared by co‐decomposition of two organometallic precursors, Fe[N(Si(CH3)3)2]22 and (η4‐1, 5‐cyclooctadiene)(η6‐1, 3, 5‐cyclooctatriene)ruthenium(0) (Ru(COD)(COT)), under dihydrogen at 150 °C in mesitylene. A series of FeRu nanoparticles of sizes of approximately 1.8 nm and incorporating different ratios of iron to ruthenium were synthesized by varying the quantity of the ruthenium complex introduced (Fe/Ru=1:1, 1:0.5, 1:0.2, and 1:0.1). FeRu nanoparticles were characterized by TEM, high‐resolution TEM, and wide‐angle X‐ray scattering analyses. Their surface was studied by hydride titration and IR spectroscopy after CO adsorption and their magnetic properties were analyzed by using a superconducting quantum interference device (SQUID). The FeRu nanoparticles were used as catalysts in the hydrogenation of styrene and 2‐butanone. The results indicate that the selectivity of the nanoparticle catalysts can be modulated according to their composition and therefore represent a case study on fine‐tuning the reactivity of nanocatalysts and adjusting their selectivity in a given reaction.